Needs Analysis for Physics E-Module Development on Work and Energy Materials in Senior High School - Aldilla, Endang; Ulfa, Jufiani; Desnita, Desnita; Usmeldi, Usmeldi (Universitas Muhammadiyah Makassar, 2023)
In today's developments, the role of educators is not only needed in terms of sharing knowledge with students but also in preparing teaching media and materials that can help accelerate the delivery of material. The purpose of this study was to explore the needs analysis in developing physics e-modules on work and energy material for class X Senior High School. This study employed surveys under quantitative and qualitative approaches. There were 153 students involved in this study. The quantitative data were collected through learning resources and learning media instruments, while qualitative data were collected using interview instruments, questionnaires, observation, analysis of procedures and survey document. The results of this study showed that most of the learning resources and teaching materials used by teachers in schools were printed books with a score of 81%, and the most frequently used media in teaching was PowerPoint media with a score of 41.67%. This fact resulted in the lack of students’ interest in solving everyday problems and low students’ learning outcomes. In other words, the learning media used in the classroom did not suit their needs, so the development of teaching materials and media is needed to facilitate students in learning activities independently. Teaching Work and Energy materials that are widely applied in everyday life requires media in the form of physics e-modules. The development of physics e-modules on work and energy materials can overcome the problems found in the classroom, especially when teaching that material.